Languages in Sub-Saharan Africa in a broader socio-political perspective - Záhořík, Jan (Acta Orientalia Vilnensia, 2010)
Charles University This study deals with language policies in Africa with a special focus on multi-ethnic and multi-lingual states including Sudan, Ethiopia, Nigeria, Cameroon, and Democratic Republic of Congo. The study will thus examine relations between state and minorities, the status of major and marginalized languages, the roles of European languages in politics as well as theoretical frameworks. Sub-Saharan Africa has undergone a remarkable process from linguistic imperialism to linguistic pluralism and revivalism. Until the 1960s the superior position of the European languages (English, French, and Portuguese) was evident, but after the Africanization of politics and society in many African countries, a strong accent on linguistic emancipation was initiated. Nowadays, many African countries follow the principle of linguistic pluralism where several languages enjoy the same rights and space in the media, administrative, education, etc. This study will discuss some important case studies and their specific language policies.